2007
DOI: 10.1016/j.seizure.2007.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Epilepsy: Public knowledge and attitude in a slum area of Karachi, Pakistan

Abstract: Considerable gaps exist in the community's knowledge about epilepsy. Some of these may explain the prevalence of negative attitudes towards this ailment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
28
4
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 18 publications
3
28
4
2
Order By: Relevance
“…This was relatively higher to those reported among general population from India, Malaysia, and Pakistan. 11,19,20 For the question "do you think epilepsy is contagious?" our results were better than the other Indian studies.…”
Section: Discussionmentioning
confidence: 99%
“…This was relatively higher to those reported among general population from India, Malaysia, and Pakistan. 11,19,20 For the question "do you think epilepsy is contagious?" our results were better than the other Indian studies.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, family beliefs about epilepsy can have significant influence on both children and family. The social misbelief about epilepsy-induced disability may affect adaptation of children and parents with epilepsy (12). Studies have shown that children with epilepsy are at high risk to suffer from behavioral and emotional problems such as depression, anxiety, obsessive, and social anxiety as well as attention and learning problems (13), while the number of research done on the effects of epilepsy on family members and other caregivers are so few (10,14).…”
Section: Introductionmentioning
confidence: 99%
“…The concept of not marrying an epileptic person was also affirmed by the M. Shafiq and his colleagues in their study in Karachi. 18,25 A review of the literature from developing countries also has suggested that people with epilepsy experience problems with education, marriage, social isolation, and employment. The evidence to date is that in both the developed and developing countries, epilepsy is perceived as stigmatising.…”
Section: Discussionmentioning
confidence: 99%
“…25 Reports from studies conducted in Nigeria, Africa, and Kenya also show that people with epilepsy are discriminated against on the grounds that epilepsy is considered to be infectious. 18 According to our study majority (55%) of respondents were educated up to matriculation while 14% were graduated.…”
Section: Discussionmentioning
confidence: 99%